Penggunaan Extended Kalman Filter Sebagai Estimator Sikap pada Sistem Kendali Servo Visual Robot - Noor Cholis Basjaruddin (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2011)
Extended Kalman Filter (EKF) is the non-linear version of Kalman filter and the said filter is usually used in nonlinear state estimation. In this study EKF is applied to process the image features of a single camera mounted on the end effector of a robot. Data generated by the EKF then is to be processed to obtain the motion parameters. Simulation of visual servo control system was built with the aim to examine the use of the EKF as a pose estimator. The simulation results using Matlab show that the EKF is able to well estimate the robot pose.